Effect of simulated digestion on the phenolic components of red grapes and their corresponding wines - Lingua, Mariana Soledad (2018)
The aim of this study was to evaluate the effect of the simulated gastro-intestinal (GI) digestion on the phenolic profile and the antioxidant capacity (AC) of grapes and red wines. Mouth and stomach digestion increased the bioaccesibility of TP (total polyphenols) in grapes, while in wine these compounds were already bioaccessible. Intestinal digestion reduced the bioaccessible polyphenols of grapes and wines, mainly due to the alkaline pH of the digestive fluid. Only 16% and 52% of the initial TP in grapes and wine, respectively, were found after assay (dialysed plus nondialysed fractions). Moreover, 21% and 39% of grape and wine AC, respectively, was conserved. In spite of the significant loss of polyphenols during digestion, both grapes and red wine still retain AC. Anthocyanins were less affected by human GI tract. Therefore, they could be the most relevant compounds to explain the AC of both grapes and red wine after GI.